The Surigao iron ore and its metallurgical treatment - Ostrea, Enrique
Mining industry provides the necessary supply of valuable metallic and non-metallic materials for global consumptions. Metallurgical industry processes the ore for distribution to different industrial plant. The existence of these two significant industries is imperative to the benefit of the general public, especially here in the Philippines where the land is rich of mineral resources. The three technical papers presented in this issue feature some of the important applications in the field of mining and metallurgical engineering. The two articles written by Professor Enrique Ostrea tackle the potential benefits of the gold refinery and the proposed metallurgical treatment in the production of pig iron for steel manufacturing in the country. Professor Ostrea, who played an active part in the development of mining and metallurgical engineering in the Philippines, strongly believed that these kinds of undertakings will be profitable and essential to the government. Unfortunately, we are not able to fully capitalize this kind of proposition. The article written by Dr. Manolo Mena described the reduction behavior of nickel in high iron. The pioneering role of mining and metallurgical engineering in national development is inevitable. With the mandate of corporate social responsibility and the advocacy of sustainability, the mining and metallurgical industries will provide economic benefits and at the same time follow compliance in the other aspects at stake on the operation such as environmental, social, health and safety. It is therefore a challenge for every sectors involved; the government, the mining and metallurgical industries, the engineers, the local government units and the socio-civic organizations to fully maximize the use of our resources.
Keywords: Iron ore -- Metallurgical analysis -- Philippines (Surigao)